Serum concentration of soluble adhesive molecules in patients with different forms of coronary artery disease - Damnjanović Goran; Jelić Marija; Đinđić Boris; Ilić Stevan (Vojnosanitetski Pregled)
Background/Aim. Vascular cell adhesion molecules-1 (VCAM-1) and intercellular cell adhesive molecules-1 (ICAM- 1) play an important role in developing and progression of coronary atherosclerosis. The aim of the paper was to compare concentrations of soluble forms of VCAM-1 and ICAM-1 in patients with different clinical presentations of coronary artery disease (CAD) and patients without CAD. Methods. Blood samples were taken from 25 patients with acute myocardial infarction (AMI), 25 patients with unstable angina pectoris (UAP), 25 with stable angina pectoris (SAP) and from 15 control patients without CAD, and concentrations of solubile adhesive molecules (VCAM-1, ICAM-1) were determined. Results. Obesity was more prominent in the NAP than in the SAP and the control patients (p < 0.05). There were no significant differences in gender distribution, age, duration of the CAD and body mass index between the groups. Hypertension and diabetes mellitus type 2 were more frequent in the CAD patients than in the controls (p < 0.01). Family history of the CAD was more frequent in the AMI and the UAP group than in the controls (p < 0.05). Serum concentrations of VCAM-1 was similar in the patients with AMI (955.9 ± 117.8 ng/mL), UAP (952.4 ± 139.1 ng/mL) and SAP (931 ± 169.8 ng/mL), and significantly higher in these groups compared with the controls (823.4 ± 97.6; p < 0.05, p < 0.05 and p < 0.1 respectively). Serum concentration of ICAM-1 was similar in the patients with AMI (699.2±125.6 ng/mL), UAP (727.6±171.8 ng/mL) and SAP (697.5±165.6 ng/mL), and significantly higher in these groups compared with the controls (583.4 ± 86.6; p < 0.1, p < 0.05 and p < 0.1 respectively). Conclusion. Increased concentrations of VCAM-1 and ICAM-1, as markers of inflammation, showed the importance of inflammatory processes in development of atherosclerosis and clinical expression of CAD. Measurement of soluble ICAM-1 and VCAM-1 concentrations is a useful indicator of atherosclerosis presence but not severity of CAD clinical presentation.